Reducing dietary intake of added sugars could affect the nutritional adequacy of vitamin A in adolescents: the Costa Rica case - Rafael Monge-Rojas; Luis A. Barboza; Rulamán Vargas-Quesada (BMC, 2023)
Abstract Background In countries where sugar fortification with vitamin A is mandatory, strategies to reduce the prevalence of overweight/obesity in adolescents that involve lowering added sugar intake could lead to vitamin A inadequate intakes, since vitamin A-fortified sugar for home consumption contributes to a high proportion of this vitamin intake in the adolescent diet. Methods The study employed a hierarchical linear model to perform a mediation analysis on a cross-sectional sample of adolescents (13-18 years old) in the province of San José, Costa Rica. Results Lowering the total energy intake derived from added sugars to less than 10% significantly increases the prevalence of vitamin A inadequate intake in adolescents by 12.1% (from 29.6% to 41.7%). This is explained by the mediation model in which, the reduced adequacy of vitamin A intake is mediated by a reduction in total energy intake derived from added sugars fortified with vitamin A. Conclusions The vitamin A fortification of sugar for household consumption should be reassessed according to the current epidemiological profile in Costa Rica to promote strategies that reduce the prevalence of overweight/obesity in adolescents by lowering the consumption of added sugars without affecting vitamin A intake.